Computational Modelling of Lead Based Mixed Halide Perovskite Solar Cells: An Advanced Study - K. Deepthi Jayan; Varkey Sebastian (New Visions in Science and Technology Vol. 3, 2021)
Perovskite solar cells (PSCs) have become a bright spot in the photovoltaics field due to the significant advancements in renewable energy and solar cell technology. Despite the fact that this relatively new technology has a bright future in using solar energy for electricity generation, its cost-effective commercialization requires extensive research. Computational modelling and simulation studies are useful in estimating the efficiency and stability of PSCs by simulating experimental circumstances in a virtual environment. SCAPS-1D software is used to simulate and analyse the performance of various Perovskite Solar Cells (PSCs) with a variety of back contact metals, electron transport layers and hole transport layers. This study describes the performance of PSCs with the mixed halide perovskites, CH3NH3PbI3-XBrX for X=1,2, as absorber layers by employing IGZO and CuSCN as the electron and hole transport layer respectively. The main objective of the study is to identify the device configuration with the best possible photovoltaic parameters and optimize the performance of the device further through a modelling study. The device configuration FTO/IGZO/CH3NH3PbI3-XBrX/CuSCN/Au for X=1 shows the best performance with a PCE of 15.40% and FF of 65.69%. For the CH3NH3PbI3-XBrX absorber layer, with X=1, the optimum defect density is found to be 1×1014 cm-3. For PSCs with CH3NH3PbI3-XBrX as absorber layer with X=1, the optimum dopant density is found to be 1.0×1014 cm-3.